Analysis of changes in urban mobility in Bogotá, D.C.: a case study based on data from the mobility observatory (2019–2023) and recommendations for measuring its impact on public policy - Lugo Garzón, Ivonne Katherine; Ferro Escobar, Roberto (Ingeniería Solidaria, 2025)
This study examines the transformations in Bogotá’s urban mobility between 2019 and 2023 through a detailed analysis of data provided by the Bogotá Mobility Observatory. Objective: to analyze changes in Bogotá’s urban mobility between 2019 and 2023 using data from the Mobility Observatory and to develop recommendations that enhance the measurement and effectiveness of public policies, contributing to a more sustainable and efficient urban transportation system. Methodology: The study is based on a comparative review and analysis of mobility data collected by the Bogotá Mobility Observatory for the years 2019 and 2023. Key indicators include levels of vehicular congestion, average travel times, traffic accident rates, and the adoption of alternative transportation modes such as bicycles and public transit. Results: The analysis indicates significant improvements in Bogotá’s urban mobility during the study period. Between 2019 and 2023, vehicular congestion decreased by 20%, while the use of public and non-motorized transport modes—particularly bicycles—increased by 25%. These changes suggest a shift toward more sustainable mobility practices in the city. Conclusion: The observed improvements reflect the effectiveness of recent mobility policies and infrastructure developments in Bogotá. The data point to a trend toward a safer, more sustainable urban transportation system, with increased reliance on alternative mobility solutions. Originality:This study offers a unique perspective by focusing on the evolution of Bogotá’s urban mobility over a five-year span, highlighting the influence of public policies and post-pandemic behavioral changes on transportation patterns. Limitations: The study is subject to certain limitations. It relies exclusively on data collected through surveys conducted by the Bogotá Mobility Observatory. While this data provides valuable insights into public perception and mobility trends, it may be affected by self-reporting biases or inaccuracies inherent to survey methodologies.